Contribuição à educação ambiental: a construção da consciência ecológica em alunos do ensino fundamental - Garavello, Juliana Previdelli (Universidade Federal de São Carlos, 2009)
The present research is a qualitative-quantitative study, involving participative-actionresearch and descriptive procedures, achieved through analysis of empirical knowledge and field (practical) research. The object of the research is the aquatic bio-indicator organisms, mainly fish, related to Environmental Education. It was intended to demonstrate that their identification is an important collaborating strategy in the construction of ecological awareness of the subjects aimed in this study, students from 5th to 8th year of grade school in private schools in the City of São Carlos, SP. The specific methodological procedures used were environmental study activities; lectures; technical visits, having one of them happened in the presence of the subjects (excursion through the course of Córrego do Gregório); material sampling; laboratory identification. The results obtained in terms of achieving the intended objectives are lists of reminiscent bio-indicator organisms in Córrego do Gregório and Ribeirões Feijão and Monjolinho, which suffer human antropic influence, emphasizing those which are good indicators of environmental quality. Through interfaces with Environmental Education, the study has motivated children to the construction of the ecological awareness and socio-environmental a responsibility, having contributed to the construction of concepts and values which are interconnected to the environmental area under the light of ethics and solidarity.
Contribution to Environmental Education: The construction of ecological awareness of educated children of elementary school
Keywords: Ecologia; Educação ambiental; Organismos aquáticos; Peixes - bioindicadores; Gregório, Córrego do (São Carlos, SP); Aquatic organisms, Bioindicator fish; Environmental education; CIENCIAS BIOLOGICAS::ECOLOGIA